USE AND PECULIARITIES OF PHRASEOLOGICAL UNITS IN ENGLISH (Academicia Globe: Inderscience Research, 2021)
This article provides information on the specific features of phraseological units in Uzbek and English languages and their use in figurative and figurative expressions. There is also research by linguists on the study of English phraseology.